OPTIMALISASI LEGALITAS UMKM MELALUI PENDAMPINGAN LEGALITAS USAHA PANGAN INDUSTRI RUMAH TANGGA/P-IRT DI DESA CILINAYA MATARAM - Makiah Makiah; Ni Made Purnami (ITEBIS PGRI Dewantara Jombang, 2025)
This Community Service Program (PKM) aims to enhance the capacity of Micro, Small, and Medium Enterprises (MSMEs) in Cilinaya, Mataram through training on business legality (Home Industry Food License/P-IRT) and digital marketing. The main issues faced by partners are limited knowledge of licensing procedures and inadequate digital marketing skills. The program was implemented in three stages—preparation, training, and monitoring and evaluation—using a participatory mentoring approach. The results show significant improvement in participants’ understanding of P-IRT application procedures and their ability to utilize social media and online marketplaces for product promotion. Many participants have begun preparing licensing documents and developing digital content. This program demonstrates that collaboration between academia, local government, and entrepreneurs effectively strengthens village economic competitiveness and fosters MSME independence through technology-based empowerment.